BEHAVIORAL PITFALLS IN FINANCIAL DECISION-MAKING: INVESTIGATING REPRESENTATIVENESS BIAS IN ACCOUNTS PAYABLES AND RECEIVABLES AMONG ENTREPRENEURS IN GOLAGHAT DISTRICT - Jyoti, Amar; Bhowal, Amalesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the impact of representativeness bias on financial decision-making among 367 entrepreneurs in Golaghat District, Assam. The analysis reveals significant influences on accounts payables, with 68% (p = .000) prioritizing past relationships with suppliers over current financial assessments. For accounts receivables, 62% (p = .000) based credit decisions on historical customer relationships rather than current creditworthiness. The Chi-square test confirms strong associations between accounts payables and receivables strategies and representativeness bias (p = 0.000). A neural network analysis achieves perfect classification with an AUC of 1 and low cross-entropy errors (0.103 for accounts payables, 0.039 for accounts receivables), demonstrating high model accuracy. Key predictors, such as "Align with historical patterns" (normalized importance: 100%) and "Ensure fairness and consistency" (normalized importance: 86.4%), are identified. The findings validate the hypotheses that representativeness bias significantly affects both accounts payables and receivables, emphasizing the need for a balanced approach in credit management practices among entrepreneurs. The study highlights the effectiveness of advanced analytical methods, such as neural networks, in modeling complex relationships in entrepreneurial financial decision-making.